Public Health Research Methods for Partnerships and Practice, 1st edition - Melody S., Goodman (Routledge, 2020)
Translating research into practice involves creating interventions that are relevant to improving the lives of a target population. Community engaged research has emerged as an evidence-based approach to better address the complex issues that affect the health of marginalized populations.